Sesame Workshop - Final Report (eKitabu, 2023)
This report outlines the project milestones, deliverables, and lessons learned from the collaborative effort between eKitabu and Sesame Workshop to adapt six 'I Heart Elmo' episodes into Rwandan Sign Language (RSL) and audio description, aiming to provide accessible edutainment for children with hearing and visual disabilities in Rwanda.
Keywords: Org:eKitabu